Transforming Cybersecurity Through Artificial Intelligence - Muralinathan, Srinath (International Journal of Research in Interdisciplinary Studies, 2025)
As the cyber threats become more complex and widespread, the classical measures of cybersecurity cannot be expected to keep pace. New entrants into the striking arena are the artificial intelligence (AI) technologies for revolutionizing cybersecurity, including, but not limited to, threat detection, incident response automation, and risk assessments. The AI systems can process vast amounts of data in a very short time, rather finding anomalies and threats with better precision than traditional techniques. With machine learning models, network traffic could be monitored for patterns to predict and prevent possible cyber-attacks, malware, and mitigate against phishing. Plus, AI-enabled security automation would reduce human interference, thereby speeding up response time and cutting operational costs. However, some challenges still need to be addressed regarding the adversarial AI, the data privacy concerns it brings, and the explainability of models, making them safe and ethical for use. This paper discusses how AI is changing the face of cybersecurity through its benefits, challenges, and future perspectives on how resilient defense mechanisms will evolve against the maturing cyber threats.